Automatic control of color sorting and pick/place of a 6- dof robot arm - Jie, Lim WeI; Sen, Teoh Poh; Normaniha, Abd Ghani (2021)
This work focuses on the implementation and design of a six degree of freedom, 6-DOF control of automatic color sorting and pick and place tasks for a robot arm using wireless controlling interface – Blynk apps. The robot arm able to differentiate the colors of the object (input) and categories or classified the object to the correct places. The main target of this project is to provide a stable, efficient, and precision results without any vibration or jittering from the servo motor during controlling the robot arm. In this work, six servo motors were used to realize the real robotic arm for industrial use. Five servos were operated to control the entire robot arm motion including the base, shoulder, and elbow as well as one servo is reserved for the positioning of the end effector. Two input variables namely TSC3200 Color Sensors & HC-SR04 Ultrasonic Sensors were employed as the input for the robot arm. The output variable mainly focused on the servo motor as the links for the robot arm to reposition and change the motion for the entire system.